Treatment of longitudinal stent compression under intravenous ultrasound guidance: A case report. Issue 51 (December 2017) - Si, Daoyuan; Yang, Hongliang; Liu, Guohui; Tong, Yaliang; He, Yuquan
Abstract: Rationale: Longitudinal stent compression is a rare phenomenon, which has been increasingly reported in recent years. Patient concerns: Following 2 stents implanted into the middle and proximal segments of the left anterior descending (LAD) artery, longitudinal stent compression occurred when a post-dilation balloon was introduced into the proximal stent opening. Diagnose: The intravenous ultrasound (IVUS) examination revealed overlapping at the opening of the proximal stent and poor stent adherence. Interventions: Another balloon was carefully inserted into the opening for post-dilation, followed by angiography and IVUS examination. Outcomes: The IVUS examination indicated that the overlapping at the opening of the proximal stent was improved and the stents were well adhered. Lessons: Such compression may be prevented by gentle and careful balloon maneuverability and improved with the use of additional balloon angioplasty or stent implantation.